Co-infection and co-localization of Kaposi sarcoma-associated herpesvirus and Epstein-Barr virus in HIV-associated Kaposi sarcoma: a case report - Julius, Peter; Kang, Guobin; Siyumbwa, Stepfanie; Musumali, Jane; Tso, For Yue; Ngalamika, Owen; Kaile, Trevor; Maate, Fred; Moonga, Phyllis; West, John T.; Angeletti, Peter; Wood, Charles (Frontiers in Cellular and Infection Microbiology, 2023)
This case report investigates the co-infection and co-localization of Kaposi sarcoma-associated herpesvirus (KSHV) and Epstein-Barr virus (EBV) in Kaposi sarcoma (KS) from the conjunctiva. KS is a vascular neoplasm that frequently affects various body regions in HIVpositive individuals. Immunohistochemistry (IHC), polymerase chain reaction (PCR), and EBV-encoded RNA in situ hybridization (EBER-ISH) were utilized in this study to demonstrate the presence of both viruses in the KS lesion. The findings demonstrated that KSHVpositive cells were also infected with EBV. In addition, multicolor immunofluorescence staining confirmed the co-localization of KSHV Latency-Associated Nuclear Antigen (LANA) and EBV Epstein Barr virus Nuclear Antigen-1 (EBNA1) within the same lesion, indicating the possibility of interactions between these gamma herpes viruses. Important questions are raised regarding the potential contribution of EBV co-infection to the development and progression of KS, necessitating additional research to determine whether such coinfection is a prevalent occurrence or an opportunistic event. This study is appropriate for submission to the Frontiers in Cellular and Infection Microbiology -Virus and Host journal due to its novel observational and investigative methods, which provide valuable insights into potential co-infection in KS and the role of viral interactions in the disease.